(untitled) (Gragoatá, 2017)
Livro resenhado: AZEVEDO, Álvares. Literatura e civilização em Portugal. Roberto Acízelo de Souza (Ed.). Rio de Janeiro: Caetés, 2016. — DOI: http://dx.doi.org/10.22409/gragoata.2017n43a926.